THIRTY-TWO YEARS OF CORRECTIVE FEEDBACK IN LANGUAGE TEACHING AND LEARNING: A REVIEW OF THE LITERATURE - Mahmood, Rizgar Qasim (LLT Journal: A Journal on Language and Language Teaching, 2022)
Corrective feedback has been one of the controversial topics in second language acquisition, L2 learning, and teaching. Corrective feedback could be in written or oral forms. Much has been written and published on this debatable topic. The purpose of the current study is to review the most cited published articles from 1990 to 2022. Reviewing research on CF has several benefits. First, researchers who are interested in investigating CF gain access to a synthesized and chronological review of the topic, and it provides insights to conduct future research on CF from different perspectives and theories. Secondly, L2 teachers can gain a clear understanding of CF, and learn about different methods and strategies for providing it to their learners alongside the results and conclusions from the previous studies. Finally, it is a ready-made review for those who cannot obtain the available studies on CF, and they have the access to refer to the previous studies once they conduct further research on CF.